Main challenges to concrete recycling in practice - Badraddin, A. K.; Abdul Rahimi, Abdul Rahman; Almutairi, Saud; Esa, Muneera (MDPI, 2021)
While concrete recycling is crucial to protecting the environment, its implementation in practice is low in many countries. This study aims to highlight challenges to concrete recycling. To achieve that aim, the study objectives are (1) to identify the main challenges to concrete recycling in construction projects; (2) to compare the main challenges between small–medium enterprises (SMEs) and large enterprises (LEs); and (3) to determine the underlying groups among the main challenges. Potential challenges were identified through a systematic literature review of journal articles and semi-structured interviews with fifteen industry practitioners. Then, the identified challenges were inserted into a questionnaire survey and distributed to industry practitioners. Eighty-nine valid responses were collected and analyzed using the mean score ranking, normalization, agreement analysis, and factor analysis techniques. The analyses show thirteen main challenges to concrete recycling. The main challenges include increased project duration, lack of national programs, lack of comprehensive rules and regulations, increased project cost, low demand for recycled concrete, low cost-effectiveness of concrete recycling, and increased transportation cost. However, there is no consensus on the criticality between SMEs and LEs. For example, increased project cost is the main challenge for SMEs but is only middlingly ranked for LEs. Finally, the main challenges can be categorized into three interrelated groups: people and technical, legal and environmental, and economic challenges. This study contributes to the literature by analyzing challenges that hinder concrete recycling in practice. The findings allow researchers and practitioners to develop strategies to reduce concrete recycling rejection.